PURIFICATION OF NICKEL SULFATE SOLUTIONS RESULTED FROM THE LEACHING OF MIXED HYDROXIDE PRECIPITATE (MHP) BY SOLVENT EXTRACTION USING VERSATIC 10 AND NICKEL-LOADED CYANEX 272 - Putra Rianto, Anugrah
The demand for nickel sulfate is predicted to increase along with the growing market of electric vehicles as one of the precursor materials for the cathode of lithium-ion battery, which is currently the first choice battery for electric vehicles. The precursor material is used in the form of nickel sulfate hexahydrate, which can be obtained from the crystallization of nickel-rich sulfate solutions. These solutions can be obtained from mixed nickel-cobalt hydroxide precipitate (MHP) by leaching the MHP and purifying the pregnant leach solution (PLS) by solvent extraction (SX). In this study, purification of the PLS solution was carried out by SX using Versatic 10 and nickel-loaded Cyanex 272 (Ni-Cyanex 272), which was used to reduce the amount of sodium in the final nickel sulfate solution to increase the purity of the nickel sulfate solution.